Mapping Nitrogen Loading in Freshwater Systems: Using Aquatic Biota to Trace Nutrients - Motitsoe, Samuel Nkopane (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
The majority of river systems in developing countries like South Africa, are found in catchments areas that are densely human populated, therefore are subjected to intense land-use and developmental pressures. Anthropogenic nutrient pollution or the excessive addition of nutrients is one important type of stressors that river systems often experience through intense land-use, which includes poor waste management and agricultural practices. Such events are referred to as the "urban syndrome" , were human populations and developmental demands outpace ecosystem services. Traditional measurements of water quality (e.g. physicochemical and micro-nutrient assessments) and biological monitoring (e.g. South African Scoring System 5, SASS5) techniques for assessing ecosystem health have being widely used to reflect the ecological health and status of river systems. However these techniques have a number of challenges associated with their application. SASS5 which is used most prevalently in southern Africa for example, can only be applied in lotic systems, it is habitat dependent and finally (but arguably most importantly) it cannot identify the source of pollution inputs. Recent laboratory studies using stable isotopic ratios (Î´15N and Î´13C) of aquatic macrophytes (duckweed: Spirodela sp.) have shown successful differentiation between different N-sources and the mapping of temporal and spatial nitrogen dynamics in freshwater systems. Furthermore Î´15N isotopic values of Spirodela sp. showed the capability to act as an early warning indicator of eutrophication, before the onset of aquatic ecosystem degradation. Therefore, this study aimed to field test the potential of sewage plume mapping using the stable isotopic values of Spirodela sp. and aquatic macroinvertebrates at nine study sites on the Bloukrans-Kowie River and ten study sites on the Bushman-New Year's River systems in the Eastern Cape, South Africa. And more...
Keywords: Uncatalogued